2019
DOI: 10.3390/microorganisms7080217
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Potential Effects of Host Genetics and Probiotic Treatment on the Gut Bacterial Community Composition of Aquaculture-raised Pacific Whiteleg Shrimp, Litopenaeus vannamei

Abstract: This study presents the potential effects of the genetic background and use of probiotics on the gut bacterial composition of Pacific whiteleg shrimp (Litopenaeus vannamei) grown in an indoor aquaculture facility. The strains investigated were Shrimp Improvement Systems (SIS, Islamorada, FL, USA), a strain genetically selected for disease resistance, and an Oceanic Institute (OI, Oahu, HI, USA) strain, selected for growth performance. BioWish 3P (BioWish Technologies, Cincinnati, OH, USA) was the selected prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…Hence, the changes in both morphological and physiological development along with feed adjustments during the early life stages could cast an impact on the bacterial communities. In addition to developmental stages, several previous studies have highlighted that shrimp genetic background can also influence their bacterial composition 37,42 . In this study, we consistently observed that the bacterial profiles within the same family were clustered together in each life stage, suggesting that the genetic variation from different shrimp families could underlie the bacterial diversity observed in shrimp population, but the effect is not as substantial as host developmental stages.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the changes in both morphological and physiological development along with feed adjustments during the early life stages could cast an impact on the bacterial communities. In addition to developmental stages, several previous studies have highlighted that shrimp genetic background can also influence their bacterial composition 37,42 . In this study, we consistently observed that the bacterial profiles within the same family were clustered together in each life stage, suggesting that the genetic variation from different shrimp families could underlie the bacterial diversity observed in shrimp population, but the effect is not as substantial as host developmental stages.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an increasing number of studies have revealed that approximately 99% of the microbial community in the environment is uncultured, which limits the applications of traditional culture methods. With the development of molecular biology technology, the non-culture method based on high-throughput sequencing technology allows a comprehensive and accurate understanding of microbial community structures in the environment and provides a new way to study their diversity and function [15,16,17]. High-throughput sequencing is mainly performed through sequencing by synthesis (SBS) and the exclusive reversible termination of chemical reactions; therefore, large amounts of data can be obtained in a short time, with high throughput, high accuracy, and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, genetic differences between HR and FG shrimp may not be expressed as different microenvironmental conditions in the digestive tract (particularly in the hepatopancreatic zone), leading to the harboring of similar microbiota regardless of the shrimp genetic profile. Genetic lines for high-resistance to pathogens or better growth performance have been used for the last two decades (Gitterle et al, 2005) and a previous study suggested that the genetic profile of L. vannamei can be an important factor in gut bacterial composition (Landsman et al, 2019). However, the results of this experiment indicate that neither enhanced resistance to pathogens nor better growth performance is associated with significant modifications in the shrimp microbiota, at least in the hepatopancreatic zone.…”
Section: Discussionmentioning
confidence: 85%